Matty Matheson : a cookbook - Matheson, Matty (Abrams, 2018)
Television chef Matty Matheson is known as much for his amazing food as his love for life, positive mental attitude, and epic Instagram account. This debut cookbook is about Matty's memories of the foods that have defined who he is. With a drive to share his zest for life, he creates dishes within these pages that reinterpret the flavors of his youth in Canada, as well as the restaurant fare for which he has become so well-known. Interpretations of classics like Seafood Chowder, Scumbo: Dad's Gumbo, and Rappie Pie appear alongside restaurant recipes like Bavette, Pigtail Tacos, and his infamous P & L Burger. This is a very personal cookbook, full of essays and headnotes that share Matty's life -- from growing up in Fort Erie, exploring the wonders of Prince Edward Island, struggling and learning as a young chef in Toronto, and, eventually, his rise to popularity.